Psycho-Social Profile of Iranian Adolescent Addicts - Mersedeh Sami'ei; Hassan Rafi'ei; Hamid Reza Taheri-Nakhost (University of Social Welfare and Rehabilitation Sciences, 2002)
Objective: This research was conducted to determine some characteristics of Iranian adolescent (<20 yrs.) addicts, including their sex, age of onset, type of abused drug, root of administration, history of cessation, family situation, socio-economic situation, psychiatric symptoms, attempted suicide, and perceived cause of being addict. Materials & Methods: Among 500 clients of an outpatient addiction treatment center in Tehran, 65 persons whose ages were not more than 20 year old, were selected and the above mentioned factors were extracted from their records. Results: Of them 98.46% were male. The least age of onset was 8. The most frequent abused drugs were opium and or heroin (79.99%). The most common root of administration was smoking (43.18% for opium and 57.14% for heroin). Seventy-six and ninety three percent of subjects had a history of cessation for at least one time. Disadvantaged socio-economic status (73.84%) and dysfunctional familial relations (60.00%) were also seen among them. All of the subjects had psychiatric symptoms (anxiety and / or depression) at the time of interviewing, while 21.53% of those had a history of admission in a psychiatric ward. Among the latter group, 28.57% also had a history of attempted suicide. The subjects' most common perceived cause for initiating use of drug was emotional familial problems (61.53%). Conclusion: The relative large contribution of youth among Iranian addict population (13%), especially along with an absolute high rate of cessation history in them (76.93%),indicating and early onset pattern of addiction in Iran. This requires serious preventive measures that seemingly should be promoting the youth socioeconomic status, emotional-familial state and mental health. More analytic studies are necessary to confirm these descriptive findings, especially for determining the risk and protective factors of addiction in adolescence.